ESG Reporting and Capital Market Investors: Insights from the Global Technology and Fintech Industries - Horobeţ Alexandra; Mnohoghitnei Irina; Belaşcu Lucian; Croitoru Ionuț Marius (Studies in Business and Economics, 2023)
This research investigates the evolving nexus between sustainability practices and firm market value, with a specific focus on the rapidly growing Fintech sector. As concerns about environmental, social, and governance (ESG) issues continue to gain prominence, understanding the implications of sustainability efforts on firm performance becomes crucial. This study proposes an empirical exploration of how sustainability initiatives, embedded in ESG scores, undertaken by Fintech firms influence their market valuations. Moreover, the investigation contrasts the findings for the Fintech firms against those for their counterpart Technology firms for the period between 2011 and 2021. The results show that Technology firms are better valued than their Fintech counterparts, which might reflect a perception of higher risk for the later. By employing panel econometric techniques in the system-GMM setting, the paper finds that capital market investors include ESG factors in their valuation of Fintech and Techinology companies, but the environmental and governance-related initiatives at corporate level are most important in this process. The study seeks to contribute to both the theoretical understanding of the sustainability-market value relationship and the practical insights relevant to Fintech firms and their stakeholders.